2020
DOI: 10.1111/jfb.14574
|View full text |Cite
|
Sign up to set email alerts
|

Application of machine learning to identify predators of stocked fish inLake Ontario: using acoustic telemetry predation tags to inform management

Abstract: Understanding predator–prey interactions and food web dynamics is important for ecosystem‐based management in aquatic environments, as they experience increasing rates of human‐induced changes, such as the addition and removal of fishes. To quantify the post‐stocking survival and predation of a prey fish in Lake Ontario, 48 bloater Coregonus hoyi were tagged with acoustic telemetry predation tags and were tracked on an array of 105 acoustic receivers from November 2018 to June 2019. Putative predators of tagge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…A paper by Klinard et.al. (2021) revealed a 17% false positive rate, utilising the larger V9 tags, and this could impact our study as well. However, based on the movement (lack of movement) of predated smolts and the findings by Halfyard et al (2017) showing that false positives first were observed after 47 days for the V5 tag, we argue this is not likely to be a substantial source of error in this study.…”
Section: Discussionmentioning
confidence: 81%
“…A paper by Klinard et.al. (2021) revealed a 17% false positive rate, utilising the larger V9 tags, and this could impact our study as well. However, based on the movement (lack of movement) of predated smolts and the findings by Halfyard et al (2017) showing that false positives first were observed after 47 days for the V5 tag, we argue this is not likely to be a substantial source of error in this study.…”
Section: Discussionmentioning
confidence: 81%
“…A VPS requires close spacing of numerous receivers and can only normally cover a small proportion of a study area, particularly in the presence of macrophytes (Espinoza et al, 2011; Steel et al, 2014), whereas Lake Macquarie is the largest coastal lagoon in Australia, with extensive seagrass beds along its eastern shore. Fish would only need to move a few hundred metres to occupy adjacent habitat to avoid detection within the VPS array, so the reduction in detections we observed over time may have been a result of predation on released fish, which is difficult to differentiate from dispersal (Sherwood et al, 2004), although “predation tags” that can detect predation on tagged fish (e.g., Klinard et al, 2021) may help to distinguish mortality from dispersal.…”
Section: Discussionmentioning
confidence: 99%